Answer:
![x^{2}+y^{2} +4x-2y+1=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%2By%5E%7B2%7D%20%2B4x-2y%2B1%3D0)
Step-by-step explanation:
we know that
The general form of the equation of a circle is
![x^{2} +y^{2}+ Dx + Ey + F=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2By%5E%7B2%7D%2B%20Dx%20%2B%20Ey%20%2B%20F%3D0)
where D, E, F are constants
step 1
Find the radius of the circle
Remember that the distance from the center to any point on the circle is equal to the radius
so
the formula to calculate the distance between two points is equal to
substitute the values
step 2
Find the equation of the circle in standard form
![(x-h)^{2} +(y-k)^{2}=r^{2}](https://tex.z-dn.net/?f=%28x-h%29%5E%7B2%7D%20%2B%28y-k%29%5E%7B2%7D%3Dr%5E%7B2%7D)
In this problem we have
center ( -2,1)
radius r=2 units
substitute
![(x+2)^{2} +(y-1)^{2}=2^{2}](https://tex.z-dn.net/?f=%28x%2B2%29%5E%7B2%7D%20%2B%28y-1%29%5E%7B2%7D%3D2%5E%7B2%7D)
![(x+2)^{2} +(y-1)^{2}=4](https://tex.z-dn.net/?f=%28x%2B2%29%5E%7B2%7D%20%2B%28y-1%29%5E%7B2%7D%3D4)
Step 3
Convert to general form
![(x+2)^{2} +(y-1)^{2}=4\\ \\x^{2}+4x+4+y^{2}-2y+1=4\\ \\x^{2}+y^{2} +4x-2y+1=0](https://tex.z-dn.net/?f=%28x%2B2%29%5E%7B2%7D%20%2B%28y-1%29%5E%7B2%7D%3D4%5C%5C%20%5C%5Cx%5E%7B2%7D%2B4x%2B4%2By%5E%7B2%7D-2y%2B1%3D4%5C%5C%20%5C%5Cx%5E%7B2%7D%2By%5E%7B2%7D%20%2B4x-2y%2B1%3D0)
Answer:
You want to divide 78 by 4, so the answer will be 17.
And to check, 17x4=78, so it is correct.
Well if you are given the radius, you can solve for it. As the volume of a cylinder is area of the base which is a circle times it height.
B • h = Pi r ^2 • h = 392 cm^3.
H = 392/Pi r^2.
This is the height or length.
Answer: F) 180°
Step-by-step explanation:
The sum of any two adjacent angles of a parallelogram is equal to 180°.